Dual controlled release compound system of PTH (1-34) as well as preparation method and application of dual controlled release compound system

Through the composite system of PLGA microspheres and nHA-CS hydrogel scaffolds, dual controlled release of PTH (1-34) is achieved, which solves the problem of sustained release of PTH (1-34) therapeutic drugs in bone defects, matches the bone healing stage, improves bone repair effects and reduces the risk of blood calcium fluctuations.

CN120661434AActive Publication Date: 2025-09-19HOSPITAL OF STOMATOLOGY SUN YAT SEN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510770149.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-10
Publication Date
2025-09-19
Estimated Expiration
2045-06-10

Smart Images

  • Figure CN120661434A_ABST
    Figure CN120661434A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biological medicine, and provides a dual controlled release compound system of PTH (1-34) and a preparation method and application thereof, the dual controlled release compound system comprises a hydrogel scaffold and PTH (1-34)-loaded microspheres loaded on the hydrogel scaffold; the PTH (1-34) loaded microsphere comprises a microsphere matrix and parathyroid hormone loaded on the microsphere matrix, and the microsphere matrix is composed of a sustained-release polymer. The invention has the following advantages: (1) the PLGA, the HA and the CS have a synergistic effect to form a dual-controlled-release composite scaffold, and the composite scaffold is combined with PTH (1-34) to form a precise controlled-release composite system; the degradation dynamics of the composite scaffold meets the requirement of a bone regeneration time window, and the composite scaffold has high physiological suitability; and (2) a repair system with a three-in-one function of'dual controlled release composite scaffold-microenvironment regulation-anatomical form matching 'is constructed, and has a remarkable curative effect on bone defect repair under pathological load repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedicine, and more specifically, to a PTH (1-34) dual-controlled-release composite system, a preparation method, and an application thereof. Background Art

[0002] Sufficient bone volume is not only the basis for the initial stability of implants, but also the key to maintaining aesthetics and function. At present, alveolar bone defects are still the key factor restricting the success of implants. Bone biomaterials can effectively induce initial cell adhesion, proliferation and differentiation, and subsequent tissue formation in both in vitro and in vivo environments. Osteoporosis has evolved into a multidimensional public health challenge. As a systemic bone metabolic disease, osteoporosis poses a challenge to oral implant treatment. Due to the low density of bone cells, limited migration of endogenous cells, and weak regenerative potential, the regeneration of alveolar bone defects in patients with osteoporosis is more challenging, and targeted bone biomaterials have shown their necessity.

[0003] Parathyroid hormone (PTH) is one of the few approved prescription bone-forming enhancers worldwide. As a core regulator of bone metabolism, it promotes anabolic bone remodeling through a triple mechanism: inhibiting pre-osteoblast apoptosis, promoting its proliferation, and inducing differentiation of bone lining cells into active osteoblasts, thereby enhancing cell function and prolonging their lifespan. The PTH(1-34) fragment, through activation of the PTH(1-34)R1 receptor, upregulates the Wnt / β-catenin pathway to promote osteoblast differentiation while inhibiting osteoblast apoptosis. Clinical studies have shown that intermittent low-dose PTH(1-34) administration significantly improves bone mineral density, outperforming traditional antiresorptive drugs, while continuous high-dose administration promotes bone resorption. The short half-life of PTH(1-34) (approximately 5 minutes) and the serum calcium fluctuations associated with systemic administration limit its clinical application. Studies have indicated that the critical time window for PTH(1-34) administration is early intervention within one week of bone defect formation. Considering the temporal patterns of bone healing, PTH therapy lasting 2-4 weeks can achieve optimal therapeutic effects. Therefore, controlled release of PTH (1-34) is a key challenge in bone defect treatment, and existing PTH (1-34) therapeutics often have ineffective local release. Therefore, developing a product that can achieve sustained local delivery of PTH (1-34) during bone repair is of great significance. Summary of the Invention

[0004] The present invention aims to overcome at least one defect (shortcoming) of the above-mentioned prior art and provide a dual controlled-release composite system of PTH (1-34), a preparation method and an application thereof, through which the controlled release of PTH (1-34) drug is achieved.

[0005] One object of the present invention is to provide a dual controlled-release composite system of PTH (1-34),

[0006] The invention comprises a hydrogel scaffold and PTH (1-34)-loaded microspheres loaded on the hydrogel scaffold; the PTH (1-34)-loaded microspheres comprise a microsphere matrix and parathyroid hormone loaded on the microsphere matrix, and the microsphere matrix is ​​composed of slow-release polymers.

[0007] Furthermore, the sustained-release polymer is polylactic acid-glycolic acid copolymer, and the material of the hydrogel scaffold is chitosan mixed with nano-hydroxyapatite.

[0008] In this technical solution, polylactic acid-glycolic acid copolymer (PLGA), which is composed of lactic acid (LA) and glycolic acid (GA) connected by ester bonds, has good biocompatibility and biodegradability, and can transport proteins, bacterial or viral DNA and various drugs in the form of microspheres, nanoparticles, etc.

[0009] Nanohydroxyapatite (nHA), with its morphology and size highly similar to HA crystals found in natural bone tissue, precisely mimics the micro- and nanostructures of the bone matrix. This biomimetic design not only imparts biocompatibility and osteoinductive activity comparable to natural bone tissue to 3D-printed scaffolds, but its unique geometric properties also ensure uniform dispersion and suspension stability of nHA within the printing ink, significantly improving the controllability of the printing process and the uniformity of the scaffold structure.

[0010] Chitosan (CS) is a natural amino polysaccharide with excellent biocompatibility and biodegradability, promoting the adhesion and proliferation of various tissue cells. The amino groups on the chitosan (CS) molecular chain stabilize the nHA dispersion system through electrostatic interactions, and its inherent flexibility effectively compensates for the brittleness of nHA. The rigidity of nHA, on the other hand, enhances the mechanical strength of the CS matrix. The two work synergistically to form an ideal composite material that combines hardness, compressive strength, and flexibility. This hydroxyapatite-chitosan (nHA-CS) composite system not only makes it an ideal bone regeneration scaffold due to its biomimetic properties, but also makes it an excellent drug controlled-release carrier due to its porous structure and surface activity.

[0011] Furthermore, the nano-hydroxyapatite is in the shape of short rods with a diameter of 20 to 45 nm and a length of 50 to 170 nm.

[0012] Furthermore, the mass ratio of the nano-hydroxyapatite to chitosan is (6-8):(2-4), preferably 7:3.

[0013] Another object of the present invention is to provide a method for preparing any of the above-mentioned dual controlled-release composite systems, comprising the following steps:

[0014] S1. Preparation of PTH (1-34)-loaded microspheres, comprising:

[0015] S11, dissolving parathyroid hormone and polyvinyl alcohol in water to form a parathyroid hormone solution and a polyvinyl alcohol solution, respectively; dissolving polylactic acid-co-glycolic acid in dichloromethane to form a polylactic acid-co-glycolic acid solution; while the polylactic acid-co-glycolic acid solution is vortexed, adding the parathyroid hormone solution, mixing, and forming colostrum;

[0016] S12, adding the colostrum to the polyvinyl alcohol solution, stirring and mixing to emulsify again, collecting the precipitate, washing, and freeze-drying to obtain PTH (1-34)-loaded microspheres;

[0017] S2. preparing chitosan ink, comprising: adding chitosan to an acid solution and mixing, adding a cross-linking modifier and mixing, then adding nano-hydroxyapatite powder and mixing, and removing bubbles to obtain chitosan ink;

[0018] The preparation of a dual controlled-release composite system of S3 and PTH (1-34) comprises:

[0019] S31. Dispersing the PTH (1-34)-loaded microspheres obtained in step S1 in the chitosan ink obtained in step S2, mixing, and removing bubbles to form a chitosan-based composite ink. The chitosan-based composite ink is 3D printed and freeze-dried to obtain a dual controlled-release composite system of PTH (1-34).

[0020] In one or more embodiments of the present invention, PTH (1-34) is selected from PTH (1-34).

[0021] Furthermore, in step S11, the polylactic-co-glycolic acid solution is vortexed at a speed of 2500 rpm to 3500 rpm, and the mixing is ultrasonic mixing, with an ultrasonic mixing time of 60 to 90 seconds. Preferably, the vortexing speed is 3000 rpm, and the ultrasonic mixing time is 60 seconds.

[0022] Furthermore, in step S12, the freeze-drying time is 12 to 18 hours.

[0023] Furthermore, in step S2, the acid solution is a mixed solution of acetic acid, lactic acid and pure water, and the volume ratio of acetic acid, pure water and lactic acid is (1.5-2.5):(1.5-2.5):(0.5-2.5), preferably, the volume ratio is 2:2:1,

[0024] Furthermore, in step S3, preferably, the air pressure of 3D printing is 80-100 kPa, and the printing speed is 60-360 mm / s; further preferably, the air pressure of 3D printing is 91-110 kPa, and the printing speed is 150-210 mm / s.

[0025] Another object of the present invention is to provide a use of any of the above-mentioned dual controlled-release composite systems or the dual controlled-release composite systems prepared by any of the above-mentioned preparation methods in the preparation of products for repairing osteoporosis or bone defects.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The present invention integrates PLGA microspheres loaded with PTH (1-34) into the nHA-CS hydrogel system, and realizes the time-controlled release of the drug through the microsphere-gel biphasic drug release system. The controlled release depends on the synergistic effect of PLGA, HA and CS. The lactic acid / glycolic acid produced by PLGA degradation modifies the CS molecular chain through hydrophobic association, reducing its hydrophilicity; nHA modifies the CS molecular chain through Ca 2+ -PO4 3- Ion exchange buffering buffers the local acidic microenvironment; nHA nanocrystals significantly increase the cross-linking density through interfacial hydrogen bonding and microspheres as physical cross-linking points, significantly delaying the disentanglement rate of polymer chain segments. The three together delay the hydrolysis process of the polymer chain and increase degradation stability, making the composite scaffold formed by PLGA, HA and CS more suitable for complex osteogenic environments.

[0028] PLGA, HA, and CS work synergistically to form a dual-controlled release composite scaffold, which, combined with PTH (1-34), forms a precisely controlled release composite system. The degradation kinetics of this composite scaffold meets the time window requirements for bone regeneration, as shown in the following: in the early stage (0-7 days), CS rapidly dissolves to release PTH (1-34), activating osteoblast differentiation; in the middle stage (7-28 days), nHA gradually dissolves to provide Ca 2+ / PO4 3- The PLGA microspheres promote mineralization; later in the course (>28 days), they continuously release the drug to maintain effective local concentrations. This three-phase release pattern closely aligns with the inflammatory, repair, and remodeling phases of bone healing, and is more physiologically compatible than a single sustained-release system.

[0029] The composite scaffold's degradation kinetics closely match the critical window for bone repair (3-6 weeks), avoiding the mechanical failure of traditional materials due to rapid degradation. This biomimetic degradation design successfully addresses the "degradation-regeneration mismatch" problem inherent in traditional materials, resulting in a significant positive correlation between the scaffold's mass loss rate and the rate of new bone deposition, providing a dynamically adaptive microenvironment for personalized bone repair.

[0030] (2) The present invention constructs a repair system with the three-in-one functions of "double controlled-release composite scaffold-microenvironment regulation-anatomical morphology matching", which has a significant therapeutic effect on the repair of bone defects under pathological load repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 Shown: physical and chemical properties of PTH (1-34) loaded microspheres; (A) microspheres under SEM; (B) particle size distribution of microspheres; (C) PTH (1-34) release curves of PTH (1-34) loaded microspheres and PTH (1-34) loaded microspheres-chitosan hydrogel.

[0032] Figure 2 Display: Selection of 3D printing parameters for composite scaffolds; (A) 4X observation of line width of PTH (1-34)-loaded microsphere-chitosan hydrogel at different pressures and printing speeds; (B) Printing speed-line width diagram of PTH (1-34)-loaded microsphere-chitosan hydrogel at different pressures; (C) Rheological viscosity test diagram of chitosan hydrogels with different hydroxyapatite ratios.

[0033] Figure 3 Shown: Construction and physical and chemical property testing of PTH (1-34) loaded microsphere-chitosan hydrogel; (A) Personalized 3D printed "CS-nHA" shaped hydrogel; (B) Electron microscopy image of PTH (1-34) loaded microsphere-chitosan hydrogel: red arrow: PTH (1-34) loaded microsphere; blue arrow: short rod-shaped nHA; (C) Rheological test image of CS hydrogel and CS-nHA hydrogel; (D) Stress-strain diagram of CS hydrogel and CS-nHA hydrogel tensile test; (E) Degradation rate of CS hydrogel, CS-nHA hydrogel, and S-CS-nHA hydrogel.

[0034] Figure 4 Shown: cell viability detection; (A) live / dead staining detection of MC3T3 cell co-culture (4X microscope image); (B) Alizarin red staining (4X microscope image); (C) CCK8 detection results; (D) ALP content detection; (E) Alizarin red semi-quantitative analysis graph; (F) osteogenic gene expression on days 3 and 7; (G) osteogenic protein blotting on days 3 and 7; (H) osteogenic protein expression on days 3 and 7.

[0035] Figure 5 Shown: (A) CT images of the sham-operated group and the experimental group; (B) bone density analysis of the sham-operated group and the experimental group; (C) BV / TV analysis of the sham-operated group and the experimental group; (D) trabecular thickness analysis of the sham-operated group and the experimental group.

[0036] Figure 6 Shows: in vivo bone formation ability detection; (A) screenshots of three-dimensional reconstruction of the skulls of three groups of rats; (B) BV analysis of the new bone formation area of ​​three groups of rats; (C) TV analysis of the new bone formation area of ​​three groups of rats; (D) BV / TV analysis of the new bone formation area of ​​three groups of rats; (E) Tb.N of the new bone formation area of ​​three groups of rats; (F) Tb.Th of the new bone formation area of ​​three groups of rats (G) Tb.Sp of the new bone formation area of ​​three groups of rats;.

[0037] Figure 7 Shown: (A) HE-stained sections of three groups of rats (4×, 10× magnification); (B) Masson-stained sections of three groups of rats (4×, 10× magnification) DETAILED DESCRIPTION

[0038] The accompanying drawings are for illustrative purposes only and are not to be construed as limiting the present invention. To better illustrate the following embodiments, some components in the accompanying drawings may be omitted, enlarged, or reduced in size, and do not represent actual product dimensions. Those skilled in the art will appreciate that some well-known structures and their descriptions may be omitted from the accompanying drawings.

[0039] Example 1

[0040] This embodiment provides a dual controlled-release composite system for PTH (1-34), comprising a hydrogel scaffold and PTH (1-34)-loaded microspheres loaded on the hydrogel scaffold; the PTH (1-34)-loaded microspheres comprise a microsphere matrix and parathyroid hormone loaded on the microsphere matrix, wherein the microsphere matrix is ​​composed of a sustained-release polymer.

[0041] The sustained-release polymer is a polylactic acid-glycolic acid copolymer, and the material of the hydrogel scaffold is chitosan mixed with nano-hydroxyapatite.

[0042] The nano-hydroxyapatite is short rod-shaped, with a diameter of 20 to 45 nm and a length of 50 to 170 nm. The mass ratio of the chitosan to the nano-hydroxyapatite is 3:7.

[0043] Example 2

[0044] This embodiment provides a method for preparing the dual controlled-release composite system of embodiment 1, the preparation method comprising:

[0045] S1. Preparation of PTH (1-34)-loaded microspheres (using water-in-oil-in-water (w / o / w) double emulsification technology):

[0046] PTH (1-34) (McLean, Shanghai, China) and polyvinyl alcohol (PVA) were dissolved in deionized water (DI), and PLGA was dissolved in dichloromethane (DCM). The PTH (1-34) solution was then added dropwise to the PLGA solution using a magnetic stirrer (Zhengzhou Biochemical) at 3000 rpm, followed by sonication for 60 s to form colostrum.

[0047] Colostrum was poured into the PVA solution and stirred with a magnetic stirrer for 3 minutes to emulsify again; stirring was continued at room temperature overnight (12 hours) to evaporate the dichloromethane, and then a planetary centrifugal stirrer was used to stir at 10,000 rpm for 4 minutes to collect the precipitate. The precipitate was collected, washed with DI, and centrifuged. This was repeated 4 times, and freeze-dried for 15 hours to obtain PTH (1-34)-loaded microspheres.

[0048] S2. Preparation of chitosan ink

[0049] An appropriate amount of chitosan powder (McLean, Shanghai, China, 6 wt% based on the total weight of the mixed acid solution) was added to a mixed acid solution (acetic acid / purified water / lactic acid, volume ratio 2:2:1) and magnetically stirred until completely dissolved, forming a homogeneous chitosan sol. Citric acid (3 wt% based on the total weight of the chitosan sol) was then introduced as a crosslinking modifier into the chitosan sol, and stirring was continued overnight (12 hours) to achieve sufficient complexation.

[0050] Short rod-shaped nano-hydroxyapatite (nHA) (Xianfeng Nano, Jiangsu, China, diameter 20-45 nm, length 50-170 nm) and chitosan sol were blended at a mass ratio of 7:3, and the nanoparticles were uniformly dispersed by high-speed shear emulsification (10,000 rpm, 30 min) in a planetary centrifugal mixer (Thinky, Japan) to obtain an ink system;

[0051] The ink system is transferred to a planetary centrifugal mixer and processed in two stages:

[0052] ① Mixing stage: 2200 rpm rotation / revolution synergy for 10 minutes to ensure system homogeneity;

[0053] ② Degassing stage: vacuum centrifuge at 2000rpm for 30s to eliminate internal microbubbles.

[0054] Finally, chitosan ink was obtained.

[0055] S3, 3D printing to form a dual controlled release composite system of PTH (1-34)

[0056] The PTH (1-34)-loaded microspheres obtained in step S1 were uniformly dispersed in the chitosan ink obtained in step S2 at a mass fraction of 10 wt% (based on the weight of the chitosan ink). A two-step process was performed using a planetary centrifugal mixer: mixing at 2200 rpm for 10 minutes, followed by vacuum degassing at 2000 rpm for 30 seconds to form a chitosan-based composite ink.

[0057] Chitosan-based composite inks were deposited layer by layer onto a pre-defined geometric pattern (40 mm long, 10 mm wide, 100 μm thick) using an envisionTEC 3D-Bioplotter bioprinter. The printing pressure was 100 kPa and the printing speed was 180 mm / s. The resulting inks were then freeze-dried at -85°C (CHRIST freeze dryer) for 12 h. After freeze-drying, the resulting inks were immersed in a 0.5 mol / L sodium hydroxide solution (room temperature, 2 h) to neutralize residual acid groups. The resulting inks were then washed three times with ultrapure water and stored in a desiccator after a nitrogen purge.

[0058] Comparative Example 1

[0059] This comparative example provides a blank composite sustained-release system, the preparation method of which differs from that of Example 2 mainly in that step S1 is the preparation of blank microspheres, and the PTH (1-34) microspheres in step S3 are replaced by blank microspheres.

[0060] Test Example 1

[0061] Chitosan-based composite inks were prepared by setting the weight ratio of nanohydroxyapatite to chitosan to 3:7, 4:6, 5:5, and 6:4, respectively. The chitosan-based composite inks and the chitosan-based composite ink provided in Example 2 were tested using a rheometer, and it was found that the viscosity of Example 2 was the best.

[0062] Test Example 2

[0063] The chitosan-based composite ink was transferred to the syringe used for printing, and a 300 μm needle was installed on the printing syringe. After the printing syringe was installed, the nitrogen gas was turned on and printing was performed at a printing pressure of 80 kPa, 90 kPa, and 100 kPa at speeds of 60 mm / min, 120 mm / s, 180 mm / s, 240 mm / s, 300 mm / s, and 360 mm / s, respectively. The width of the printing marks under the above four settings was observed under a 4× microscope.

[0064] Chitosan-based composite ink mixed with blank microspheres was used to print a special pattern CS-HA using a 3D printer and observed at room temperature to explore whether the composite ink can adapt to bone defects of complex shapes.

[0065] Test Example 3 Characterization Test

[0066] The microstructure of the dual controlled-release composite system of PTH (1-34)-loaded microspheres and PTH (1-34) was observed using scanning electron microscopy (SEM).

[0067] Rheological properties: The dynamic viscoelastic properties of pure chitosan hydrogel and chitosan-based composite ink (nHA:chitosan = 7:3) were measured using a rheometer (Anton Paar MCR302, Austria) in dynamic oscillation mode: frequency sweep 1.0 Hz, temperature 37°C (simulating physiological environment), angular velocity 5 rad / s, and storage modulus (G') and loss modulus (G").

[0068] Mechanical properties test: Long strip specimens (40 mm × 10 mm) were prepared and tensile tested using a universal testing machine (INSTRON E3000, UK) with a loading rate set at 10 mm / min-1.

[0069] In vitro degradation analysis: Samples were immersed in PBS (pH 7.4) at 37°C until swelling equilibrium was reached. The initial mass (W0) was recorded. Samples were removed from the dynamic degradation system (fresh PBS was replaced every 48 hours) at 7, 14, 21, and 28 days, and the residual mass (Wt) was measured after freeze-drying. Degradation rate calculation formula:

[0070] Degradation rate (%) = (W0-Wt) / W0×100%

[0071] Test Example 4 Drug Loading Rate and Drug Release Curve

[0072] Determination of drug loading efficiency of PTH (1-34)-loaded microspheres: Accurately weigh 10 mg of PTH (1-34)-loaded microspheres and suspend them in a mixed solvent system consisting of 1 ml of 0.9% NaCl solution and 200 μl of dichloromethane. After the sample was shaken at room temperature for 1 hour, the drug concentration in the supernatant was measured using a PTH (1-34) ELISA kit. The drug loading was calculated according to the following formula: Drug loading (%) = (drug mass in microspheres / initial dose mass) × 100%

[0073] Drug release profile of the PTH(1-34)-loaded microsphere release system: 10 mg of drug-loaded microspheres were dispersed in 3 ml of PBS (pH 7.4) and shaken in a 37°C water bath. Samples were collected at pre-determined time points (days 1, 2, 3, 4, 7, 10, 15, 20, 25, and 30). The supernatant was collected by centrifugation at 1000 rpm for 5 minutes at 4°C, and an equal volume of fresh PBS was added to maintain the system constant. PTH(1-34) levels were determined by ELISA at each time point, and cumulative release curves were plotted.

[0074] Drug release profile of a dual-controlled-release composite system for PTH (1-34): Samples of the dual-controlled-release composite system were immersed in 3 mL of PBS and subjected to release experiments under the same conditions (37°C, 1000 rpm). Samples were collected at the same time sequence, and an equal amount of fresh PBS was added immediately after each supernatant collection. PTH (1-34) content was determined by ELISA, and a time-dependent cumulative release curve was simultaneously plotted.

[0075] All experiments were performed with three parallel samples, and the data were expressed as mean ± standard deviation.

[0076] Furthermore, the PTH (1-34)-loaded microspheres are prepared according to step 1 of the method of Example 2, and the PTH (1-34) dual controlled-release composite system is provided in Example 1.

[0077] Test Example 5: Culture and experimental grouping of MC3T3-E1 cells

[0078] MC3T3-E1 cells were routinely cultured under standard culture conditions (37°C, 5% CO2, and 95% relative humidity) in α-MEM medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin (PS). Fresh medium was replaced every 48 hours, and cells were trypsinized and passaged when they reached 90% confluence. Cells in the logarithmic growth phase of passages 3-5 were used for subsequent experiments.

[0079] The experiment was divided into a negative control group (Blank), a blank microsphere-hydrogel group (PLGA / CS-nHA), and a drug-loaded microsphere-hydrogel group (PTH(1-34)@PLGA / CS-nHA). The cells in the control group were routinely cultured in complete culture medium. The other two groups were immersed in culture medium and placed in an incubator (37°C, 5% CO2 and 95% relative humidity). On the corresponding days (1d, 3d, 5d, 7d), the materials were centrifuged at 1000r / min for 5min. The supernatant was extracted and filtered with a 0.22μm filter to obtain the corresponding extract for cell culture.

[0080] Furthermore, the blank microsphere-hydrogel group (PLGA / CS-nHA) uses the blank composite sustained-release system provided in Comparative Example 1, and the drug-loaded microsphere-hydrogel group (PTH(1-34)@PLGA / CS-nHA) uses the dual controlled-release composite system of PTH(1-34) provided in Example 1.

[0081] Test Example 6 Cell Proliferation and Activity Evaluation

[0082] 1) CCK-8 assay

[0083] The cells were plated at 3 × 10 3Cells were seeded into 96-well plates. After 1, 3, 5, and 7 days of culture, basal medium containing 10% CCK-8 reagent was added to each well and incubated at 37°C in the dark for 2 h. The absorbance at 450 nm was measured using a microplate reader, and the relative cell proliferation rate was calculated.

[0084] 2) Live / dead cell double staining

[0085] Cells were seeded as before and treated with a Calcein AM (2 μM) / Propidium Iodide (PI, 4 μM) double staining kit on days 1, 4, and 7. After washing with PBS, the cells were incubated with the staining solution at 37°C in the dark for 30 min. Observation was performed under a fluorescence microscope (live cells showed green fluorescence, dead cells showed red fluorescence).

[0086] Test Example 7 In vitro osteogenic differentiation ability assay

[0087] The experiment was conducted using αMEM osteogenic medium containing 10 mM β-glycerophosphate, 0.25 mM ascorbic acid, and 10 nM dexamethasone. The effect of the drug-loaded microsphere-hydrogel system on promoting osteogenic differentiation of MC3T3 cells was systematically evaluated through alkaline phosphatase (ALP) activity analysis, mineralized nodule staining, and osteogenic marker detection. The drug-loaded microsphere-hydrogel system in this test example is the dual controlled-release composite system for PTH (1-34) provided in Example 1.

[0088] 1) Alkaline phosphatase detection

[0089] MC3T3 cells (1×10 5 Cells were divided into groups and treated 24 hours later: the control group received osteogenic culture medium, while the experimental groups received PLGA / CS-nHA and PTH(1-34)@PLGA / CS-nHA extracts (preparation methods described in Test Example 5). The culture medium was refreshed every 48 hours. Quantitative analysis of the ALP assay kit was performed using the cell lysate extract at 4, 7, and 14 days after intervention, with absorbance at 405 nm measured using a microplate reader.

[0090] Furthermore, the PLGA / CS-nHA is the blank composite sustained-release system provided in Comparative Example 1, and the PTH(1-34)@PLGA / CS-nHA is the dual controlled-release composite system of PTH(1-34) provided in Example 1.

[0091] 2) Mineralization capacity assessment

[0092] A 6-well plate system (1×10 5Cells were cultured for 21 days and washed with PBS before staining with Alizarin Red S (0.2%, pH 4.2, room temperature for 30 minutes). After observing calcium nodule formation under a light microscope, 10% cetylpyridinium chloride solution (1 mL / well) was added to dissolve the staining complex. 150 μL of the solution was transferred to a 96-well plate, and absorbance was measured at 562 nm to establish a semi-quantitative analysis model for mineralization deposition.

[0093] 3) Osteogenesis-related gene testing

[0094] RT-qPCR detection system: 24-well plates were inoculated with cells (1×10 4 The intervention protocol was the same as described in section 1). Total RNA was extracted using the TRIzol method on days 3 and 7 after intervention, and cDNA was obtained by reverse transcription. The expression of marker genes such as Alp, Runx2, Col1, and Ocn was detected using the SYBR Green assay, using GAPDH as an internal control.

[0095] 4) Osteogenesis-related protein detection

[0096] Western blotting analysis: Cells were treated as described in section 3). Total proteins were collected and subjected to SDS-PAGE electrophoresis (12% separating gel). After transfer, the membrane was blocked with 5% skim milk and incubated with primary antibodies against RUNX2 (1:1000), ALP (1:800), and COL1 (1:1500) overnight at 4°C. After incubation with HRP-conjugated secondary antibodies (1:5000) for 1 hour at room temperature, protein expression was detected using an ECL imaging system.

[0097] Test Example 8 Animal Experiment

[0098] All animal experiments were approved by the Institutional Animal Care and Use Committee of Sun Yat-sen University (approval number: SYSU-IACUC-2024-000724) and conducted in strict accordance with the Guidelines for Ethical Review of Laboratory Animal Welfare. The skull defect model of osteoporotic rats was used to evaluate the function of drug-loaded microsphere-hydrogel. Ten-week-old female SD rats (n=15) were selected and randomly divided into three groups (n=5 / group): blank control group (sham operation, Blank), PLGA / CS-nHA group, and PTH(1-34)@PLGA / CS-nHA group. The PLGA / CS-nHA group used the blank composite sustained-release system provided in Comparative Example 1; the PTH(1-34)@PLGA / CS-nHA group used the dual controlled-release composite system of PTH(1-34) provided in Example 1.

[0099] 1) Surgical modeling process

[0100] Ovariectomy (OVX): Laparotomy was performed through a dorsal approach. After locating both ovaries, the blood vessels 0.5-1 cm proximal to the uterine horns were ligated and the ovaries were removed.

[0101] Sham operation control: the same incision was performed to expose the ovary but the intact organ was preserved.

[0102] Model validation: Twelve weeks after surgery, some rats in the OVX and sham-operated groups were randomly killed, and the femurs were obtained for micro-CT scanning. The trabecular volume fraction (BV / TV) and bone mineral density (BMD) were used to quantitatively confirm the successful establishment of osteoporosis model.

[0103] 2) Skull defect model and intervention

[0104] Surgical procedure: After anesthesia, the soft tissue of the skull vault was incised to expose the parietal bone. A 5-mm circular bone drill was used to symmetrically create full-thickness bone defects at the sagittal-lambda suture junction. The blank group (no material was placed) and the experimental group (PLGA / CS-nHA and PTH(1-34)@PLGA / CS-nHA composite systems were filled, respectively) and the soft tissue was sutured in layers. Four weeks after surgery, skull specimens were obtained and fixed with 4% paraformaldehyde for 24 hours. The defect area was reconstructed three-dimensionally by micro-CT (scanning resolution 10 μm), and the new bone volume (BV), relative new bone volume (BV / TV), trabecular number (Tb.N), trabecular thickness (Tb.TN), and trabecular separation (Tb.Sp) were quantified. Paraffin sections were prepared after 30 days of EDTA decalcification and stained with H&E and Masson's trichrome.

[0105] All experiments were performed with biological replicates of n ≥ 3 to meet statistical power requirements. Normally distributed data are presented as mean ± standard deviation (SD). One-way ANOVA was performed using GraphPad Prism 9.4.1 (GraphPad Software). Homogeneity of variance was confirmed by Levene's test, and differences between groups were determined using Tukey's multiple comparison method. A p value < 0.05 was considered statistically significant.

[0106] The following is an analysis of the results of the above experiments.

[0107] 1. Synthesis, Printing, and Characterization of a PTH(1-34) Dual Controlled Release Composite System (PTH(1-34)@PLGA / CS-nHA)

[0108] In this study, PTH (1-34)-loaded microspheres were prepared using a water-in-oil-in-water (w / o / w) double emulsion technique. The resulting microspheres were in the form of white powder and stored at -20°C to maintain the drug's biological activity. Field emission scanning electron microscopy (FE-SEM) characterization revealed ( Figure 1A), the microspheres have smooth surface, regular morphology, monodisperse spherical structure, uniform particle size distribution, and average particle size: 79.03±8.19μm ( Figure 1 B), with good monodispersity and no significant agglomeration. Quantitative analysis using enzyme-linked immunosorbent assay (ELISA) showed that the drug loading rate of the microspheres reached 68.2%, demonstrating a high drug encapsulation capacity.

[0109] In vitro sustained-release experiments showed that ( Figure 1 C): The microsphere group (PTH(1-34)@PLGA) showed a burst release of 30.8±1.3% within the initial 24 hours, while the PTH(1-34)@PLGA / CS-nHA group showed a significantly reduced burst release of 19.4±2.1% (p<0.01), representing an 11.4% decrease compared to the PTH(1-34)@PLGA system. Both systems exhibited significant sustained-release properties, maintaining a stable linear release trend over 30 days. By the end of the 30-day experiment, the cumulative release of the PTH(1-34)@PLGA group reached 75.2±1.5%, while that of the PTH(1-34)@PLGA / CS-nHA group was 71.8±1.7%. The release curve then entered a plateau phase. This improved sustained-release performance is attributed to the physical restriction of drug diffusion by the hydrogel network. This is highly consistent with the critical time window for PTH (1-34) treatment proposed by Long et al. (early intervention is initiated within 7 days after bone defect, and the duration of treatment is controlled at 2-4 weeks). This system maintains the effective concentration of PTH (1-34) within 30 days, which can provide continuous stimulation for early bone repair.

[0110] The above-mentioned article by Long et al. on the critical time window for PTH treatment is: Long, J. et al.

[0111] Dual-Cross-Linked Magnetic Hydrogel with Programmed Release of Parathyroid Hormone Promotes Bone Healing. ACS Appl. Mater. Interfaces 15, 35815-35831 (2023).

[0112] The PTH(1-34)@PLGA / CS-nHA composite scaffold constructed in this study exhibits unique dual controlled-release properties stemming from a dual barrier effect: the nHA network delays CS segment hydrolysis through ion exchange, while the acidic microenvironment generated by PLGA microsphere degradation triggers protonation of CS amino groups, forming dynamic crosslinking points to inhibit swelling. This pH-responsive degradation behavior intelligently matches the local inflammatory microenvironment of the bone defect (early pH↓, late pH↑), ensuring synchronized drug release with tissue regeneration. This dual controlled-release mechanism not only effectively reduces the clinical risk of fluctuating blood calcium concentrations but also enables localized and sustained delivery of PTH(1-34) during bone repair, providing a stable osteogenic stimulation microenvironment for bone repair.

[0113] This study revealed the dynamic mechanical response characteristics and enhancement mechanism of the CS / nHA composite system through multi-scale rheological characterization. When CS was compounded with short rod-shaped nanohydroxyapatite (nHA, diameter 20-45nm, length 50-170nm) in a mass ratio of 3:7, rheological tests showed that its storage modulus (G') was improved by an order of magnitude (from 10 2 -10 3 Pa increased to 10 3 -10Pa), the loss modulus (G") shows a synchronous growth trend ( Figure 3 C). This significant viscoelastic transition confirms the formation of a multi-level physical cross-linked network between the rod-shaped nHA crystals and the CS molecular chains. The high aspect ratio of nHA not only enhances the network topology through steric hindrance, but its surface hydroxyl groups also form hydrogen bonds with CS amino groups, jointly constructing a dynamic network system with energy dissipation capabilities. After entering the plateau phase, the storage modulus of the CS-HA hydrogel exceeded 10 kPa, indicating that it possesses moderate mechanical strength. This moderate mechanical strength maintains the structural integrity of the bone scaffold while avoiding the cellular stress shielding effect caused by excessive rigidity, meeting the application requirements of bone regeneration scaffolds. After uniformly dispersing PTH (1-34)-loaded microspheres in the CS-nHA matrix, the final printing ink was obtained. After freeze-drying for 12 hours, the resulting scaffold had a volume shrinkage of <2%, demonstrating excellent stability.

[0114] Shear rate sweep experiments further confirmed that the composite ink has excellent shear response characteristics ( Figure 2 C): At low shear rates (0.1 s-1), the apparent viscosity reaches 4.45 × 10 mPa·s, giving the material solid-like behavior and preventing structural collapse. However, at high shear rates (100 s-1), the viscosity drops rapidly to 1.12 × 10 mPa·s, exhibiting a significant shear-thinning effect (a decrease of 97.5%), which provides the necessary conditions for continuous extrusion of the ink.

[0115] Based on the system optimization of orthogonal experimental design, the study established the optimal parameter combination of air pressure (100kPa) and nozzle movement speed (180mm / min). This condition successfully achieved the spatiotemporal matching of extrusion dynamics and deposition dynamics: the ink wire width was stable at 675.14±11.3μm (CV<5%, n=3), ensuring excellent shape fidelity ( Figure 2 A, B). Microstructural analysis showed that nHA exhibited a three-dimensional interpenetrating arrangement in the CS matrix ( Figure 3 B), this biomimetic mineralized structure provides an ideal topological microenvironment for cell adhesion. Through a multi-dimensional correlation analysis of rheology, process, and structure, this study resolved the inherent contradiction between extrudability and conformability of hydrogel inks. The resulting PTH(1-34)@PLGA / CS-nHA composite system not only meets the mechanical requirements of bone tissue engineering scaffolds, but its micron-scale printing precision and submicron-scale topological features also create a biomimetic microenvironment for directional cell migration and bone tissue regeneration. These findings provide a reliable design paradigm for the development of intelligent bone repair materials with bioactive delivery capabilities.

[0116] Clinically, since the morphology of bone defects in patients is often irregular, bone augmentation scaffolds need to be prepared individually. Therefore, this study personalized the preparation of CS-nHA hydrogel into a special shape of "CS-nHA" ( Figure 3 A), fully demonstrating that the 3D printed scaffold can accurately adapt to the complex defect contour and can well meet the needs of clinical applications. Its excellent plasticity is due to the shear thinning properties of CS-nHA ink ( Figure 2 C). SEM observation shows ( Figure 3 B): The surface of the composite scaffold showed significant topological heterogeneity. Drug-loaded microspheres (particle size 79.03±8.19μm) and short rod-shaped nHA (diameter 20-45nm, length 50-170nm) were discretely and evenly distributed in the CS matrix, and no phase separation was observed. The discretely distributed nHA / microsphere composite structure on the scaffold surface simulated the multiphase characteristics of natural bone tissue (Havers system and bone pits). This spatial distribution pattern confirmed that the system has a highly homogenized phase-separation-free structural characteristic. This topological feature may promote drug release and cell-scaffold interaction by increasing the specific surface area26.

[0117] The study successfully constructed a functionalized composite system by uniformly dispersing PTH (1-34)-loaded microspheres (drug loading rate 68.2%) in a chitosan-short rod-shaped nanohydroxyapatite (CS-nHA, mass ratio 3:7)-based bioink. The short rod-shaped nHA (50-170 nm in length, 20-45 nm in diameter) formed a three-dimensional physical cross-linked network through hydrogen bonding and electrostatic interactions between surface hydroxyl (-OH) groups and chitosan amino (-NH) groups. This network significantly improved the ink stability, with a 24-hour microsphere sedimentation rate of <5%. By printing pre-designed scaffolds, real-time monitoring showed a line width deviation rate of <3% (set value vs. measured value). The scaffold volume shrinkage after freeze-drying was not significantly different from the freshly printed state, indicating that the drying process did not disrupt the microsphere-matrix interface.

[0118] By introducing short rod-shaped nHA (length 50-170 nm, diameter 20-45 nm), the ultimate tensile stress of the CS-HA composite material increased by 96.8% (18.5±3.2→36.4±3.5 kPa) and the tensile strain increased by 41.8% (25.1→35.6%) ( Figure 3 D) This mechanical enhancement is attributed to the uniform dispersion of short rod-shaped nHA and the strong interfacial hydrogen bonding network formed between the rod-shaped nHA and chitosan chains. The high aspect ratio of short rod-shaped nHA imparts excellent stress transfer efficiency. Compared to spherical nHA, the rod-shaped crystals have a larger specific surface area and better orientation, resulting in improved mechanical properties of the composite.

[0119] In vitro degradation experiments showed that ( Figure 3 E), on the 7th day of degradation, the mass of the three groups of hydrogels decreased, and then the degradation of the pure CS group accelerated. During the 28-day degradation period, the pure CS group showed an exponential degradation curve due to deacetylation (degradation rate 71.16±0.45%), while the CS-nHA group showed an exponential degradation curve due to the Ca 2+ -PO4 3- The buffering effect (pH stable at 6.8±0.3) reduced the degradation rate to 50.12±0.65%. After the introduction of PLGA microspheres, the degradation rate of the PTH(1-34)@PLGA / CS-nHA group was further reduced to 47.87±0.71%, and its linear degradation kinetics was more consistent with the time window required for bone regeneration. This is attributed to the triple synergistic effect: the lactic acid / glycolic acid produced by PLGA degradation modified the CS molecular chain through hydrophobic association, reducing its hydrophilicity; nHA modified the CS molecular chain through Ca 2+ -PO4 3-Ion exchange buffering mitigates the local acidic microenvironment; nHA nanocrystals significantly increase crosslinking density through interfacial hydrogen bonding and microspheres as physical crosslinking points, significantly slowing the disentanglement rate of polymer chain segments. The three together slow down the hydrolysis process of the polymer chain, increase degradation stability, and make the composite scaffold more suitable for complex osteogenic environments. The degradation kinetics of the composite scaffold are synergistically regulated by the nHA content and the distribution of PLGA microspheres: in the early stage (0-7 days), CS rapidly dissolves and releases PTH (1-34), activating osteoblast differentiation; in the middle stage (7-28 days), nHA gradually dissolves to provide Ca 2+ / PO4 3- Promotes mineralization; later (>28 days), PLGA microspheres continuously release the drug to maintain a local effective concentration. This three-stage release pattern closely aligns with the inflammatory, repair, and remodeling phases of bone healing, and is more physiologically compatible than a single sustained-release system. Notably, the degradation kinetics of the composite scaffold closely matches the critical window of bone repair (3-6 weeks), avoiding the mechanical support failure caused by rapid degradation of traditional materials. This biomimetic degradation design successfully addresses the "degradation-regeneration mismatch" problem associated with traditional materials, resulting in a significant positive correlation between the scaffold mass loss rate and the rate of new bone deposition, providing a dynamically adaptive microenvironment for personalized bone repair.

[0120] 2. Cytocompatibility of the PTH(1-34) dual controlled-release composite system (PTH(1-34)@PLGA / CS-nHA)

[0121] Cytocompatibility is the primary prerequisite for the in vivo application of biomaterials. To evaluate the biological properties of materials, this study used a co-culture system of MC3T3-E1 preosteoblasts and scaffold material extracts, and conducted a systematic analysis using CCK-8 cell proliferation assays and live / dead cell staining dual evaluation methods. Quantitative analysis results showed (n=5) that the cell viability of each group showed a significant increasing trend from day 1 to day 5, among which the PTH(1-34)(1-34)@PLGA / CS-nHA group had the strongest pro-proliferation effect (P<0.05, Figure 4 C), which is due to the fact that the burst release of PTH (1-34) in this group was only 19.4 ± 2.1%, and the sustained release time of PTH (1-34) was more than 30 days ( Figure 1 C). Live / dead staining results (n=3) further confirmed the biosafety of the material: all experimental groups maintained high cell viability at 1, 4, and 7 days, and the PTH(1-34)@PLGA / CS-nHA group had significantly higher viability than the other two groups at all time points (4A), indicating that the addition of PTH(1-34) significantly promoted cell proliferation. These results fully demonstrate the excellent biosafety of the composite scaffold material, and that the addition of PTH(1-34) further enhanced the material's pro-cell proliferation effect.

[0122] 3. In vitro osteogenic differentiation ability of the dual controlled-release composite system of PTH(1-34) (PTH(1-34)@PLGA / CS-nHA)

[0123] Ideal bone repair materials must possess the ability to precisely regulate osteogenic differentiation. Alkaline phosphatase (ALP) is an early marker of osteogenic differentiation, while matrix mineralization is a key indicator of late differentiation. This study, based on verification of the material's biosafety, constructed a three-tiered evaluation system: ALP activity, ECM mineralization, and gene / protein expression. This systematically analyzed the in vitro osteogenic performance of PTH(1-34)@PLGA / CS-nHA.

[0124] ALP staining showed (n=3): ALP activity in the PTH(1-34)@PLGA / CS-nHA group increased significantly in a time-dependent manner, and by day 14, it was approximately 3.08 times higher than that in the control group (P<0.01, Figure 4 D). This rapid activation of early osteogenic markers suggests that the material may rapidly initiate osteogenic program through the cAMP-PKA pathway. Alizarin red staining at 21 days showed ( Figure 4 B), dense mineralized nodules were formed in the PTH(1-34)@PLGA / CS-nHA group, and the quantitative analysis of the mineralized area increased by 1.85 times compared with the control group (P<0.001, Figure 4 E), indicating that the material can significantly promote ECM calcium salt deposition.

[0125] RT-qPCR detection of key osteogenic markers (n=3) revealed that PTH(1-34)@PLGA / CS-nHA significantly upregulated osteogenic genes: the early marker Alp showed a significant upregulation on day 3 (3.99-fold, P<0.05) and maintained this upregulation until day 7 (5.15-fold, P<0.01); the expression of the transcriptional regulator Runx2 increased over time, reaching 6.74-fold on day 7 (P<0.001); the matrix protein Co11 and the late marker Opn were upregulated by 3.41-fold and 5.48-fold on day 7, respectively (P<0.01, Figure 4 F). Western blot results further confirmed that the protein expression levels of RUNX2, ALP and COl1 were highly consistent with the gene expression (n=3, Figure 4 GH), forming a complete gene-protein expression regulatory network.

[0126] The excellent performance of the PTH(1-34)@PLGA / CS-nHA group stems from a triple synergistic mechanism: a dual-stage controlled release system: PLGA microspheres (drug loading rate 68.2%) and CS hydrogels synergistically regulate the release kinetics of PTH(1-34), with early burst release (19.4±2.1%) rapidly initiating osteogenesis and later (2-30 days) sustained release (71.8±1.7%) maintaining efficacy, promoting osteogenesis by intermittently activating PTH(1-34)1R; microenvironment regulation: the morphology and size of the rod-shaped nHA are similar to those of HA crystals in natural bone tissue, which can better simulate the structure and function of natural bone tissue, and the short rod-shaped nHA (aspect ratio 3.8:1) continuously releases Ca 2+ / PO4 3- nHAP and PTH (1-34) have a synergistic effect during treatment. Topological mechanical signaling: The CS matrix regulates cytoskeletal tension, activating corresponding mechanical transduction pathways and promoting osteogenesis.

[0127] IV. In vivo osteogenic ability of the PTH(1-34) dual controlled-release composite system (PTH(1-34)@PLGA / CS-nHA)

[0128] To investigate the inhibitory effect of the osteoporotic microenvironment on bone regeneration and verify the repair efficacy of PTH(1-34)@PLGA / CS-nHA, this study established an ovariectomy (OVX)-induced osteoporosis rat model combined with a critical-size skull defect model (5 mm in diameter). Female SD rats (n=25) were randomly divided into an OVX group (n=20) and a sham operation group (Sham, n=5). Micro-CT three-dimensional reconstruction ( Figure 5 A) and quantitative analysis showed that bone mineral density (BMD): OVX group (0.228±0.008g / cm 3 ) compared with the Sham group (0.457±0.009g / cm 3 ) was significantly reduced by 49.9% (P<0.001, Figure 5 B); Bone volume fraction (BV / TV): OVX group (8.49±0.13%) decreased by 51.9% compared with Sham group (17.64±0.24%) (P<0.001, Figure 5 Trabecular bone thickness (Tb.Th): OVX group (0.067±0.002mm) was 31.7% less than that of Sham group (0.098±0.011mm) (P<0.001, Figure 5D); Bone microarchitecture deteriorated: In the OVX group, trabecular number (Tb.N) decreased by 58.3% (3.2±0.2 vs 1.4±0.1 / mm, P<0.001), and trabecular separation (Tb.Sp) increased by 2.1-fold (0.43±0.03 vs 0.91±0.05mm, P<0.001). These indicators combined confirmed the successful establishment of the osteoporosis model, with bone microarchitecture displaying typical high-turnover osteoporosis characteristics and a 2.8-fold increase in bone resorption rate.

[0129] Bone defect repair efficacy evaluation showed that after 4 weeks of intervention in osteoporosis rats (n=5 / group), Micro-CT three-dimensional reconstruction analysis showed significant differences between the groups: the negative control (NC) and PLGA / CS-nHA groups only showed scattered low-density images in the marginal area (new bone volume fraction BV / TV were NC group:

[0130] In the PTH(1-34)@PLGA / CS-nHA group, high-density new bone tissue was formed in the defect center (BV / TV=0.2020±0.0165); the trabecular thickness (Tb.Th, respectively: NC group: 0.3879±0.0149, PLGA / CS-nHA group: 0.3536±0.0197, PTH(1-34)@PLGA / CS-nHA group: 0.6132±0.028) was significantly higher than that in the NC group (0.3879±0.0149, PLGA / CS-nHA group: 0.3536±0.0197, PTH(1-34)@PLGA / CS-nHA group: 0.6132±0.028). 3, mm); ④Tb.N were: NC group: 0.2359±0.0485, PLGA / CS-nHA group: 0.2193±0.0386, PTH(1-34)@PLGA / CS-nHA group: 0.4867±0.0286, 1 / mm; ⑤Tb.Sp were: NC group: 5.345±0.785, PLGA / CS-nHA group: 5.296±0.675, PTH(1-34)@PLGA / CS-nHA group: 3.498±0.260, mm (P<0.001, Figure 6 AG).

[0131] Osteogenesis evaluation confirmed that PTH(1-34)@PLGA / CS-nHA exhibited significant therapeutic advantages in repairing osteoporotic bone defects. Micro-CT quantitative analysis (n=5 / group) showed that PTH(1-34)@PLGA / CS-nHA significantly outperformed the NC and PLGA / CS-nHA groups in bone regeneration indicators: bone volume fraction (BV / TV) in the PTH(1-34)@PLGA / CS-nHA group reached 0.2020 ± 0.0165, a 2.08-fold and 2.22-fold increase compared to the NC group (0.0973±0.0129) and PLGA / CS-nHA group (0.0909±0.0031), respectively (P<0.001). Trabecular thickness (Tb.Th): The trabecular structure of the PTH(1-34)@PLGA / CS-nHA group was more complete (0.6132±0.0283mm), which was 1.58 times and 1.73 times higher than that of the NC group (0.3879±0.0149mm) and the PLGA / CS-nHA group (0.3536±0.0197mm), respectively (P<0.001). Trabecular number (Tb.N): The trabecular network density of the PTH(1-34)@PLGA / CS-nHA group (0.4867±0.0286mm) was significantly higher than that of the NC group (0.3879±0.0149mm) and the PLGA / CS-nHA group (0.3536±0.0197mm). -1 ) was significantly higher than that of the NC group (0.2359±0.0485mm -1 ) and PLGA / CS-nHA group (0.2193±0.0386mm -1 ), which increased by 2.06 times and 2.22 times, respectively (P<0.001); trabecular separation (Tb.Sp): the trabecular spacing of PTH(1-34)@PLGA / CS-nHA (3.498±0.260mm) was reduced by 34.56% and 33.95% compared with the NC group (5.345±0.785mm) and the PLGA / CS-nHA group (5.296±0.675mm), respectively (P<0.001), indicating that its microstructural connectivity was significantly enhanced.

[0132] In addition to Micro-CT detection, the study also used hematoxylin-eosin (HE) and Masson trichrome staining system to evaluate the quality of bone defect repair in each group ( Figure 7HE staining analysis: At low magnification (4×), the defect areas in the NC and PLGA / CS-nHA groups were primarily filled with loose connective tissue, with only a small amount of osteoid deposits visible at the edges, and no mature bone tissue was observed. In the PTH(1-34)@PLGA / CS-nHA group, a continuous bone-like structure formed in the central region. High magnification (10×) revealed a significant increase in the number of osteoblasts, accompanied by an active bone lining cell layer. Masson staining: The defect centers in the NC and PLGA / CS-nHA groups were primarily composed of blue collagen fibers, with only scattered red bone matrix. In the PTH(1-34)@PLGA / CS-nHA group, a fully connected, continuous lamellar bone structure was observed, with abundant bone matrix visible in between. Histological results were highly consistent with the Micro-CT three-dimensional reconstruction data, confirming that the PTH(1-34)@PLGA / CS-nHA system significantly enhances the regenerative capacity of osteoporotic bone defects by promoting osteoblast activation and matrix mineralization. In summary, this study constructed a functional scaffold system suitable for the repair of osteoporotic bone defects through multi-scale structural design and pathological microenvironment regulation.

[0133] In this study, we observed incomplete bone regeneration in the skull defect area of ​​osteoporosis model rats, which may be caused by multiple factors: the inhibitory effect of the osteoporosis pathological microenvironment: the successfully constructed OVX model rats showed typical characteristics of bone metabolism imbalance: bone density (BMD = 0.228 ± 0.008 g / cm 3 ) and bone volume fraction (BV / TV = 8.49 ± 0.13%) were reduced by 49.9% and 51.9%, respectively, compared with the sham-operated group (P < 0.001), and bone microarchitecture was significantly degraded (Tb.Sp increased 2.1-fold). Under this pathological condition, the osteogenic microenvironment in the defect area is poor: proinflammatory factors are unbalanced, stem cell differentiation is shifted, the adipogenic differentiation tendency of BMSCs is enhanced, and the osteogenic-adipogenic balance is disrupted. Limitations of the therapeutic time window: The 4-week observation period set in this experiment may not be sufficient to fully reflect the bone repair potential of the composite scaffold. The current PTH (1-34) sustained-release system (30-day cumulative release rate of 71.8 ± 1.7%) does not cover the complete callus remodeling stage (including endochondral ossification, primary callus formation, and lamellar bone remodeling), resulting in insufficient new bone mass and maturity.

[0134] 5. Conclusion and Analysis

[0135] This study, through multi-scale design, has constructed a bone repair system with the trinity of "dual controlled drug release, microenvironmental regulation, and anatomical morphology matching." Compared to traditional single-component systems, this composite system exhibits significant advantages:

[0136] Dual release kinetics: PLGA microspheres (drug loading rate 68.2±3.1%) and CS / nHA hydrogel synergistically regulate PTH (1-34) release, achieving precise adaptation of early therapeutic concentration (24-hour burst release of 19.4±2.1%) and long-term maintenance concentration (cumulative release of 71.8±1.7% by 30 days);

[0137] Microenvironment regulation: The addition of short rod-shaped nHA can better simulate the structure and function of natural bone tissue. Short rod-shaped nHA and PTH (1-34) synergize in the treatment process;

[0138] Anatomical morphology matching: 3D bioprinting based on clinical CT data achieves anatomical adaptation of the defect area.

[0139] Taking these characteristics into account, this composite system improves the pathological state of the osteoporotic bone defect microenvironment. In vivo experiments conducted in an osteoporotic rat model confirmed the system's significant efficacy in repairing bone defects under pathological loads: Micro-CT quantitative analysis showed a 2.22-fold increase in the new bone volume fraction (BV / TV) compared to the control group (p<0.001), and histological analysis also confirmed this trend. These research results fully demonstrate the potential of this composite system, providing a new paradigm for optimizing the repair process of osteoporotic bone defects.

[0140] Obviously, the above embodiments of the present invention are merely examples for the purpose of clearly illustrating the technical solutions of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included within the scope of protection of the claims of the present invention.

Claims

1. A dual controlled release composite system of PTH (1-34), characterized in that: It comprises a hydrogel scaffold and PTH (1-34)-loaded microspheres loaded on the hydrogel scaffold; The PTH (1-34)-loaded microspheres comprise a microsphere matrix and parathyroid hormone loaded on the microsphere matrix, and the microsphere matrix is ​​composed of slow-release polymers.

2. The dual controlled-release composite system according to claim 1, characterized in that: The sustained-release polymer is a polylactic acid-glycolic acid copolymer, and the material of the hydrogel scaffold is chitosan mixed with nano-hydroxyapatite.

3. The dual controlled release composite system according to claim 2, characterized in that: The nano-hydroxyapatite is in the shape of a short rod, with a diameter of 20 to 45 nm and a length of 50 to 170 nm.

4. The dual controlled-release composite system according to claim 2, characterized in that: The mass ratio of the nano-hydroxyapatite to chitosan is (6-8): (2-4).

5. A method for preparing the dual controlled-release composite system according to any one of claims 2 to 4, characterized in that: The following steps are involved: S1. Preparation of PTH-loaded microspheres, including: S11, dissolving parathyroid hormone and polyvinyl alcohol in water to form a parathyroid hormone solution and a polyvinyl alcohol solution, respectively; dissolving polylactic acid-co-glycolic acid in dichloromethane to form a polylactic acid-co-glycolic acid solution; while the polylactic acid-co-glycolic acid solution is vortexed, adding the parathyroid hormone solution, mixing, and forming colostrum; S12, adding the colostrum to the polyvinyl alcohol solution, stirring and mixing to emulsify again, collecting the precipitate, washing, and freeze-drying to obtain PTH (1-34)-loaded microspheres; S2. Preparation of chitosan ink, comprising: adding chitosan to an acid solution and mixing, adding a cross-linking modifier and mixing, then adding nano-hydroxyapatite powder and mixing, and removing bubbles to obtain chitosan ink; The preparation of a dual controlled-release composite system of S3 and PTH (1-34) comprises: S31. Dispersing the PTH (1-34)-loaded microspheres obtained in step S1 in the chitosan ink obtained in step S2, mixing, and removing bubbles to form a chitosan-based composite ink. The chitosan-based composite ink is 3D printed and freeze-dried to obtain a dual controlled-release composite system of PTH (1-34).

6. The preparation method according to claim 5, characterized in that In step S11, the vortex rotation speed of the polylactic acid-co-glycolic acid solution is 2500 rpm to 3500 rpm; the mixing is ultrasonic mixing, and the ultrasonic mixing time is 60 to 90 seconds.

7. The preparation method according to claim 5, characterized in that In step S12, the freeze-drying time is 12 to 18 hours.

8. The preparation method according to claim 5, characterized in that In step S2, the acid solution is a mixed solution of acetic acid, lactic acid and pure water, and the volume ratio of the acetic acid, pure water and lactic acid is (1.5-2.5):(1.5-2.5):(0.5-2.5).

9. The preparation method according to claim 5, characterized in that In step S3 , the air pressure for 3D printing is 91-110 kPa, and the printing speed is 150-210 mm / s.

10. Use of the dual controlled-release composite system according to any one of claims 1 to 4 or the dual controlled-release composite system prepared by the preparation method according to any one of claims 5 to 9 in preparing products for repairing osteoporosis or bone defects.

Citation Information

Patent Citations

  • Dosage regimen for a controlled-release PTH compound

    CN109789189A

  • Silk fibroin and parathyroid hormone coupling grafting method and application thereof

    CN112516330A

  • Bone repair n-HA / CS porous scaffold as well as preparation method and application thereof

    CN113041403A

  • Biological scaffold, biological scaffold-microsphere sustained-release system and preparation method and application of biological scaffold-microsphere sustained-release system

    CN114504679A

  • Method for controlled release of parathyroid hormone from encapsulated poly (lactic-co-glycolic acid) microspheres

    TW201210610A